Effects of Light on Secondary Metabolite Biosynthesis in Medicinal Plants - Zhang, Shuncang; Zhang, Lei; Zou, Haiyan; Qiu, Lin; Zheng, Yuwei; Yang, Dongfeng; Wang, Youping (Frontiers in Plant Science, 2021)
Secondary metabolites (SMs) found in medicinal plants are one of main sources of drugs, cosmetics, and health products. With the increase in demand for these bioactive compounds, improving the content and yield of SMs in medicinal plants has become increasingly important. The content and distribution of SMs in medicinal plants are closely related to environmental factors, especially light. In recent years, artificial light sources have been used in controlled environments for the production and conservation of medicinal germplasm. Therefore, it is essential to elucidate how light affects the accumulation of SMs in different plant species. Here, we systematically summarize recent advances in our understanding of the regulatory roles of light quality, light intensity, and photoperiod in the biosynthesis of three main types of SMs (polyphenols, alkaloids, and terpenoids), and the underlying mechanisms. This article provides a detailed overview of the role of light signaling pathways in SM biosynthesis, which will further promote the application of artificial light sources in medicinal plant production.